A rare presentation of spinal epidural abscess - Crowest, Paul Robert Oliver (BMJ Publishing Group, 2011)
A 77-year-old retired engineer presented to accident and emergency with deteriorating shortness of breath that had been troubling him for several months. At that time, he was being investigated by a chest physician who had identified bilateral diaphragmatic paralysis on ultrasound and was awaiting further imaging. Clinical assessment and nerve conduction studies on this admission were compatible with a diagnosis of motor neuron disease but specialist neurology input recommended an MRI to rule out cord pathology. This proved problematic as the patient was non-invasive ventilation dependent and unable to lay supine as this further compromised his respiratory function. To ensure that a potentially reversible cause for his symptoms was identified, the patient was intubated for an MRI which subsequently demonstrated multi level spinal epidural empyema. The benefits of neurosurgical intervention were judged to be uncertain at best, and following discussion with the family, active care was withdrawn. The patient passed away shortly thereafter.